Pivot: Fast, Synchronous Mashup Isolation Using Generator Chains - Mickens, James (Proceedings of the IEEE Symposium on Security and Privacy, 2014)
Pivot is a new JavaScript isolation framework for web applications. Pivot uses iframes as its low-level isolation containers, but it uses code rewriting to implement synchronous cross-domain interfaces atop the asynchronous cross-frame postMessage() primitive. Pivot layers a distributing scheduling abstraction across the frames, essentially treating each frame as a thread which can invoke RPCs that are serviced by external threads. By rewriting JavaScript call sites, Pivot can detect RPC invocations; Pivot exchanges RPC requests and responses via postMessage(), and it pauses and restarts frames using a novel rewriting technique that translates each frame's JavaScript code into a restartable generator function. By leveraging both iframes and rewriting, Pivot does not need to rewrite all code, providing an order-of-magnitude performance improvement over rewriting-only solutions. Compared to iframe-only approaches, Pivot provides synchronous RPC semantics, which developers typically prefer over asynchronous RPCs. Pivot also allows developers to use the full, unrestricted JavaScript language, including powerful statements like eval().